2008
DOI: 10.1038/nm1788
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of learning deficits in a Tsc2+/− mouse model of tuberous sclerosis

Abstract: Tuberous sclerosis is a single-gene disorder caused by heterozygous mutations in the TSC1 (9q34) or TSC2 (16p13.3) gene and is frequently associated with mental retardation, autism and epilepsy. Even individuals with tuberous sclerosis and a normal intelligence quotient (approximately 50%) are commonly affected with specific neuropsychological problems, including long-term and working memory deficits. Here we report that mice with a heterozygous, inactivating mutation in the Tsc2 gene (Tsc2(+/-) mice) show def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

44
844
5
13

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 782 publications
(906 citation statements)
references
References 30 publications
44
844
5
13
Order By: Relevance
“…mTOR knockout mice (mTOR −/− mice) die in utero (21,22), and brainspecific deletion of the mTORC1 up-stream regulators Tsc1 or Pten results in death within the first postnatal weeks (15,23). Thus, the study of mTORC1 signaling in adult animals has been limited.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…mTOR knockout mice (mTOR −/− mice) die in utero (21,22), and brainspecific deletion of the mTORC1 up-stream regulators Tsc1 or Pten results in death within the first postnatal weeks (15,23). Thus, the study of mTORC1 signaling in adult animals has been limited.…”
Section: Resultsmentioning
confidence: 99%
“…12). Moreover, mice lacking either the mTORC1 negative regulator Tsc2 or the downstream targets 4e-bp2 and S6k1/2 exhibit altered synaptic plasticity and memory (13)(14)(15). However, several aspects of these results are controversial.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that these brain malformations are dysplastic rather than neoplastic, which might explain why they are not responsive to the anti-proliferative effect of rapamycin (Bissler et al, 2008). However, pre-clinical studies in several mouse models showed improvement in neurological manifestations of TSC, such as seizures, and memory and learning deficits (Ehninger et al, 2008;Meikle et al, 2008;Zeng et al, 2008). Furthermore, reduced seizure frequencies in TSC patients have been described upon treatment with rapamycin (Franz et al, 2006;Muncy et al, 2009).…”
Section: The Mtorc1 Inhibitors As Treatment For Tscmentioning
confidence: 99%
“…Treatment with the mTORC1 inhibitor rapamycin has shown promising results in PTEN knockout mice (Zhou et al, 2009) and TSC2 + /À mice (Ehninger et al, 2008). Thus, interventions that target mTOR signaling should be at the leading edge of future translational research in the autism field.…”
Section: David Feifelmentioning
confidence: 99%